Hubungan Peran Orang Tua dalam Upaya Pemeliharaan Kesehatan Gigi terhadap Kejadian Karies pada Anak Usia 6-10 Tahun - Biaz K Wirawan; Ainun Ayu Yuniar; Muh. Firdaus Tullah; Nur Aedah Ahmad Rani (Jurnal Terapi Gigi dan Mulut, 2025)
Dental caries remains a major oral health problem among children aged 6–10 years and is closely related to parental involvement in maintaining oral hygiene. This study aimed to analyze the relationship between parental role and the occurrence of dental caries in children aged 6–10 years at the Dental and Oral Hospital of Hasanuddin University, Makassar. This research employed a descriptive-analytic design with a cross-sectional approach. The study was conducted from July to August 2025. A total of 109 parent–child pairs who visited RSGMP Unhas and met the inclusion criteria were recruited using purposive sampling. Primary data were collected through interviews with parents using a structured questionnaire to assess parental roles, and direct clinical observation of children to determine dental caries status. Data were processed through editing, coding, entry, and cleaning stages. Descriptive analysis was performed to describe respondent characteristics, while the Chi-square test was used to examine the association between parental role and dental caries occurrence. The results showed that most parents had a good role in maintaining their children’s oral health (98.17%). All children examined (100%) were found to have dental caries. Statistical analysis using the Chi-square test demonstrated a significant relationship between parental role and the occurrence of dental caries, with p-value: 0.0001 (p<0.05). In conclusion, there was a significant association between parental role and dental caries in children aged 6–10 years at RSGMP Unhas Makassar. Strengthening parental involvement in oral health maintenance is essential to prevent and control dental caries in children.